Antifungal effect of sesame medicinal herb on Candida Species: original study and mini-review - Fatemeh Lavaee; Maryam Moshaverinia; Seyed Ali MalekHosseini; Akram Jamshidzade; Maryam Zarei; Hadis Jafarian; Pardis Haddadi; Parisa Badiee
The aim of this study was to evaluate the antifungal susceptibility patterns of three antifungals, methanolic extracts and N-hexane oil of sesame seeds on C. albicans and C. glabrata, isolated from oral cavity of liver transplant recipients. The results were compared with other reports to develop a mini review as well. Candida species were isolated from liver transplant recipients. To evaluate the antifungal activity of sesame seed oil and methanolic extract, fluconazole, caspofungin and nystatin, the corresponding minimum inhibitory concentrations were determined by CLSI M27-A3 standard method. Minimum fungicidal concentration was also evaluated. The most prevalent species was C. albicans, followed by C. glabrata. Findings indicated sensitivity to antifungal agents and resistance to methanolic extract and N-hexane oil for all C. albicans and C. glabrata isolates. The rate of Candida colonization in the oral cavity of liver transplant recipients was high. Our results revealed that the methanolic and N-hexan extracts of sesame seeds are not effective on C. albicans and C. glabrata species, isolated from the patients. The sesame seed oil pulling and mouthwash cannot effectively cleanse and remove the Candida species in the mouth. Investigation of other medicinal plants or other parts of sesame like leaves and roots are suggested.